2016
DOI: 10.1057/imfer.2015.43
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of Natural Resource Exports for Nonresource Trade

Abstract: Foreign exchange windfalls such as those from natural resource revenues change nonresource exports, imports, and the capital account. The paper studies the balance between these responses and shows that the response to $1 of resource revenue is, for our preferred estimates, to decrease nonresource exports by 74 cents and increase imports by 23 cents, implying a negligible effect on foreign savings. The negative per $1 impact on exports is larger for manufactures than for other sectors, and particularly large f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 54 publications
3
59
0
2
Order By: Relevance
“…This result concurs with previous findings obtained by Acosta et al . () and Harding and Venables (). This result is robust to the measurement of the resource windfall.…”
Section: Resultsmentioning
confidence: 99%
“…This result concurs with previous findings obtained by Acosta et al . () and Harding and Venables (). This result is robust to the measurement of the resource windfall.…”
Section: Resultsmentioning
confidence: 99%
“…For the heavily resource dependent countries, the mainstream literature has suggested that natural resource exploitation tends to crowd out the manufacturing industry: positive wealth shocks in the resource sector tend to appreciate the exchange rate and dampen the competitiveness of other traded sectors. As noted by Sachs and Warner (2001) resource economies tend to have higher prices, while, according to Harding and Venables (2013), the response to a positive resource shock is to drop non-resource exports in the order of 35-70 percent. Gylfason (2001) argues that since resource extraction tends to be low skill and highly mechanised, it is likely to stimulate a neglect on human capital by crowding out education, innovation, and entrepreneurship.…”
Section: Why Is African Manufacturing So Far Behind?mentioning
confidence: 98%
“…A well‐known version of the ‘resource curse’ is labelled the ‘Dutch disease’, which establishes a causal relationship between booming exports in natural resources and/or primary products – a situation leading to an appreciating real exchange rate – and deindustrialization (e.g. Corden and Neary, ; Corden, ; Matsuyama, ; Harding and Venables, ). The term ‘Dutch disease’ was first coined in 1977 by The Economist to describe the (supposedly) harmful effects on Dutch manufacturing of booming Dutch exports in natural resources after the new discovery of large natural gas reserves in the North Sea – particularly the Groningen natural gas field in 1959 – leading to a sharp inflow of foreign currency in the Netherlands and the appreciation of Dutch currency.…”
mentioning
confidence: 99%